Treatment With Schistosoma Japonicum Peptide SJMHE1 and SJMHE1-Loaded Hydrogel for the Mitigation of Psoriasis - Liu X; Wang S; Jiang Y; Luo X; Yang Y; Huo L; Ye J; Zhou Y; Yang Z; Du F; Dong L; Mao C; et al. (Psoriasis: Targets and Therapy)
Xi Liu,1,* Shang Wang,2,* Yuyun Jiang,1 Xinkai Luo,1,3 Yanwei Yang,1 Liyue Huo,1 Jixian Ye,1 Yuepeng Zhou,1 Zhe Yang,1 Fengyi Du,4 Liyang Dong,3 Chaoming Mao,3 Xuefeng Wang1,3 1Department of Central Laboratory, The Affiliated Hospital of Jiangsu University, Zhenjiang, 212001, People’s Republic of China; 2Tzu Chi International College of Traditional Chinese Medicine, Vancouver, BC, Canada; 3Department of Nuclear Medicine, Institute of Digestive Diseases, and Institute of Endocrinology, The Affiliated Hospital of Jiangsu University, Zhenjiang, 212001, People’s Republic of China; 4School of Medicine, Jiangsu University, Zhenjiang, 212013, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xuefeng Wang, Email xuefengwang@ujs.edu.cnPurpose: Harnessing helminth-induced immunomodulation offers a novel therapeutic avenue for autoimmune and inflammatory diseases; however, research on helminths against psoriasis remains limited. This study evaluates the effects of the peptide SJMHE1 from Schistosoma japonicum (S. japonicum) on the inflammatory response in imiquimod (IMQ)-induced psoriasis mice and LPS-stimulated keratinocytes, as well as the efficacy of SJMHE1-loaded hydrogel on psoriasis in mice.Methods: SJMHE1 was administered to mice with IMQ-induced psoriasis via topical administration or subcutaneous injection, and effects were evaluated by detecting the skin inflammation of mice. LPS-stimulated HaCaT cells were used to assess the regulatory effects of SJMHE1 in vitro. Additionally, the effects of Poloxamer 407 (P407)-loaded SJMHE1 were evaluated in mice with IMQ-induced psoriasis through topical application.Results: Topical administration and subcutaneous injection of SJMHE1 alleviated psoriasis-like skin lesions, improved PASI scores, reduced epidermal thickness and dermal inflammatory cell infiltration, and decreased expression of Ki67, a marker of keratinocyte proliferation or differentiation. SJMHE1 modulated pro-inflammatory and anti-inflammatory cytokine expression in LPS-treated HaCaT cells, down-regulating NF-κB and STAT3 activation. Both SJMHE1-loaded hydrogel and SJMHE1 treatment alleviated IMQ-induced psoriasis-like skin lesions, improved PASI scores, reduced the number of Ki67-positive epidermal cells, decreased the spleen index and T-cell infiltration, increased the proportion of regulatory T cells (Tregs), and decreased the percentage of Th17 cells, alongside reducing inflammatory cytokine expression and NF-κB and STAT3 activation in skin lesions. Notably, weight changes in the SJMHE1-loaded gel group were less than those in the betamethasone-positive control group on days 6, 7, and 8 post-IMQ administration.Conclusion: SJMHE1-loaded hydrogel and SJMHE1 treatment inhibited NF-κB and STAT3 activation in skin lesions, improved Th17/Treg balance, and reduced inflammatory cytokine expression in psoriasis mice, thereby ameliorating psoriatic lesion symptoms. Furthermore, SJMHE1-loaded hydrogel exhibited fewer side effects compared to betamethasone, positioning it as a promising strategy against psoriasis. Keywords: Schistosoma japonicum peptide SJMHE1, SJMHE1-loaded hydrogel, mitigation, psoriasis